Effects of Direct and Indirect Explicit Grammar Instructional Strategies on Achievement in English Grammar and Composition Among Secondary School Students in Ibadan Metropolis (2015)
English is indispensable in communication and it is a tool for learning in Nigeria. Many secondary school students perform poorly in English Language examinations because of their deficient knowledge of English grammar which in turn leads to their inability to write good composition. The use of conventional instructional strategies for learning has failed to address this problem in Ibadan metropolis. However, less attention has been paid to the use of Direct and Indirect explicit grammar instructional strategies which have been found to be more effective than the conventional instructional strategies. This study, therefore, examined the effects of Direct Explicit Grammar (DEG)and Indirect Explicit Grammar (IEG) instructional strategies on achievement in English grammar and composition among secondary school students in Ibadan metropolis. The moderating effects of class-size and gender were also determined. The study adopted a pretest-posttest, control group, quasi-experimental design using a 3x3x2 factorial matrix. Three local government areas (LGAs) were randomly selected out of the five in Ibadan metropolis and three public schools were purposively selected from each LGA (3 per LGA). Nine intact classes of 274 senior secondary II students were used for the study. The intact classes were randomly assigned to DEG,IEG and control groups respectively. Treatment lasted six weeks. The instruments used were: English Grammar Achievement Test (r=0.81), English Composition Achievement Test (ECAT r = 0.84) and Teachers Instructional Guides. Data were analysed using Analysis of Covariance and Scheffe post-hoc test at 0.05 level of significance. There was a significant main effect of treatment on students‟ achievement in English grammar (F(3,273) = 8.373; ŋ2=0.03) and English composition (F(3,273) = 5.375; ŋ2 = 0.04). These indicate weak effect size. Participants in the DEG group obtained the highest posttest achievement mean score (=21.95) in English grammar, followed by IEG (= 21.88) and control ( = 15.57) groups. Also, the participants in the DEG group obtained the highest posttest achievement mean score ( = 19.93) in English composition, followed by IEG ( = 16.47) and control ( = 12.57) groups. Class-size did not have significant main effect on achievement in English grammar but it did on composition (F(3,273)= 4.993; ŋ2= 0.04). This indicates a weak effect size. Large class ( = 15.63) obtained the highest achievement mean score followed by the medium ( = 12.26) and small class (=12.08) groups. Gender did not have significant main effect on achievement in English grammar and composition.The two-way interaction effect of treatment and class-size was significant on achievement in English composition (F(4,273) = 3.69; ŋ2 = 0.05) but not in English grammar. This indicates a moderate effect size. Direct explicit and indirect explicit grammar instructional strategies enhanced students‟ achievement in English grammar and composition in public senior secondary schools in Ibadan metropolis. Teachers should adopt both strategies in teaching English grammar and composition for improved performance